Introduction to Text Analysis: A Coursebook - Walsh, Brandon; Horowitz, Sarah (Brandon Walsh, Sarah Horowitz, 2018)
This workbook provides a brief introduction to digital text analysis through a series of three-part units. Each unit introduces students to a concept, a tool for or method of digital text analysis, and a series of exercises for practicing the new skills. In some cases, studies of particular projects are presented instead of tools in the third section of each unit. The materials here are meant to form the basis for a digital text analysis course that does not require extensive training in programming and is written with student readers in mind. Originally developed for use in a course titled “Scandal, Crime, and Spectacle in the Nineteenth Century,” this workbook draws from these course materials for its datasets and prompts. The book is intended to be modularized enough that it could be used in conjunction with other courses either in whole or in part, as all of its materials are openly available on GitHub. The tripartite structure of each chapter means that sections can be easily removed and replaced with different tools or content. In particular, we envision our course-specific exercises in the third section of each chapter to be removable. For more guidance on how to remix the work for your own ends, see Adapting This Book. Book is also available for viewing online - http://walshbr.com/textanalysiscoursebook/ - and was originally published there.
Book is also available for viewing online - http://walshbr.com/textanalysiscoursebook/ - and was originally published there
Original submission date: 2023-05-19T15:51:15Z
Keywords: Text Analysis; Text Mining; Text Analytics; Pedagogy; Digital Pedagogy; Digital Humanities